Analisis Dampak Pemanfaatan Permainan Edukasi Wordwall Terhadap Motivasi Belajar Matematika Peserta Didik Kelas III Madrasah Ibtidaiyah - Agustina, Siti Rodliyah Eka; Saputri, Zuzun Ana; Farisia, Hernik; Mualawiyah, Robiatul; Jafaar, Azhar (Diniyah: Jurnal Pendidikan Dasar, 2025)
This study aims to analyze the impact of using Wordwall educational games on the mathematics learning motivation of third-grade students at Madrasah Ibtidaiyah. The study applied a descriptive qualitative approach, utilizing questionnaires, interviews, observations, and documentation involving 22 students. Three students representing high, moderate, and low motivation levels were selected for in-depth analysis. The findings revealed that the use of Wordwall had a positive effect on improving mathematics learning motivation, with the most significant contributions seen in the indicators of perseverance and interest in learning. Highly motivated students showed improvements across all indicators, moderately motivated students experienced gains in learning interest, while students with low motivation demonstrated initial engagement but still required additional guidance. The design of the "box-opening" and "spinning wheel" games effectively encouraged active interaction and cooperative student participation. These results suggest that Wordwall can serve as a technology-based pedagogical strategy relevant to enhancing student learning motivation. This study also contributes to the growing body of literature on the effectiveness of digital educational media in primary education, particularly in mathematics learning through interactive games.Keywords: Wordwall; learning motivation; mathematics; Madrasah Ibtidaiyah; educational games.